TINJAUAN YURIDIS DEBITUR MELAPORKAN KREDITUR KE KEPOLISIAN ATAS EKSEKUSI JAMINAN FIDUSIA (Studi Kasus: Beberapa Surat Perintah Penghentian Penyidikan [SP3]) - Liana Liana; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
Social phenomenon, the debtor reports the creditor to the police after the execution of the fiduciary guarantee after the Constitutional Court Decision Number 18/PUU-XVII/2019. This research examines juridically, the criminal elements that are suspected and whether creditors can be ensnared in the intended criminal article after executing the fiduciary guarantee object. This type of research is normative-empirical, qualitative in nature, legal and case approaches (case approach), using secondary and primary data. The Constitutional Court's decision determines otherwise in terms of execution of fiduciary guarantee objects, but creditors in executing fiduciary guarantee objects follow the procedures in POJK 35/2018. In order not to cause continuous problems related to the execution of fiduciary guarantee objects after the Constitutional Court Decision, a new regulation is needed at the Police level. Because Fiduciary guarantees are a civil domain which can indeed become a criminal domain, when in its implementation other crimes occur such as violence and/or threats committed by executors or do not follow the provisions stipulated in the law.